Family reorganization after Alzheimer's disease diagnosis (Research, Society and Development, 2020)
Objectives: To understand how the reorganization and restructuring of intrafamily dynamics occurs in relation to Alzheimer's disease. Methodology: This is a qualitative, integrative review-type study, with the Virtual Health Library (VHL) as its database. The following criteria for inclusion of articles were adopted: complete materials, in Portuguese language, in the article format and with a six-year (2015 - 2020) time cut. The exclusion criteria were: materials that were duplicated and did not meet the theme. At the end of the application of the criteria described above, 10 articles emerged. Data analysis: Two thematic categories were identified: Lack of knowledge about Alzheimer's disease; Overload in the face of disease progression and coping strategies. Conclusion: The presence of the caregiver in the assistance in the daily practices is fundamental for the well-being of the elderly with AD, since for the promotion of their autonomy in the activities of daily life, it is necessary his support and supervision, guaranteeing his quality of life. And such quality of life should also be proposed to family caregivers, in the same way, they are the main promoters of healthy actions. The proposal of reception groups in health units, the elaboration of booklets with specific guidelines on AD and the offer of follow-up by the mental health team of the services are actions that can promote greater recovery and maintenance of the family caregivers' health.